2016
DOI: 10.1038/srep20367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle-Associated Bacteria from a Drinking Water Treatment Plant and Distribution Reservoirs with Different Water Sources

Abstract: This study assessed the characteristics of and changes in the suspended particles and the associated bacteria in an unchlorinated drinking water distribution system and its reservoirs with different water sources. The results show that particle-associated bacteria (PAB) were present at a level of 0.8–4.5 × 103 cells ml−1 with a biological activity of 0.01–0.04 ng l−1 ATP. Different PAB communities in the waters produced from different sources were revealed by a 16S rRNA-based pyrosequencing analysis. The quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Here the authors concluded that the observed seasonal changes in richness indicate that the most common and dominant bacterial taxa have temporally defined niches. Ling et al (2016) also suggested that the observed seasonal variation influenced the dynamics of several core populations identified in DWDS biofilms and was main driver in the overall variation in the biofilm community.…”
Section: Long-term Seasonal Variations In Microbial Communitymentioning
confidence: 92%
See 2 more Smart Citations
“…Here the authors concluded that the observed seasonal changes in richness indicate that the most common and dominant bacterial taxa have temporally defined niches. Ling et al (2016) also suggested that the observed seasonal variation influenced the dynamics of several core populations identified in DWDS biofilms and was main driver in the overall variation in the biofilm community.…”
Section: Long-term Seasonal Variations In Microbial Communitymentioning
confidence: 92%
“…The increase of bacterial richness during distribution may be associated with regrowth, particularly in large distribution systems where bulk water is transported over long distances. Microbial growth in drinking water has been observed in the form of higher particle counts and increased turbidity (Liu et al, 2016), higher cell counts (Hammes et al, 2008) and increase in the presence of indicator organisms in the final tap water compared to the water leaving the treatment plant (van der Wielen et al, 2016). The water leaving the treatment plant may therefore be impacted by the distribution system itself through processes such as pipe corrosion (Sun et al, 2014), the detachment of biofilms (Chaves Simões and Simões, 2013) and suspension of loose deposits (Liu et al, 2013;Liu et al, 2017;Liu et al, 2018).…”
Section: The Interplay Between Spatial and Temporal Dynamics Of The Dwdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there is a call for rapid detection of phenotypically diverse aquatic microbes, comprising small protists, hetero and autotrophic prokaryotes, and viruses, all showing a vast range of different sizes and morphologies (Fig. This can lead to a dramatic underestimation of the true microbial cell number in complex environmental settings (e.g., waters rich in particulate matter and microbial aggregates), bringing to misleading understanding of the system composition (12,13). The ecological interactions among microorganisms (e.g., predation, competition for resources, mutualism, and parasitism) and their metabolic performances may modulate their growth at very short space and time scales.…”
mentioning
confidence: 99%
“…In general, the problem is overcome by a strong simplification of the system, considering each detected particle as a single event, independently by its size and actual composition. This can lead to a dramatic underestimation of the true microbial cell number in complex environmental settings (e.g., waters rich in particulate matter and microbial aggregates), bringing to misleading understanding of the system composition (12,13). In other cases, complex gating supported by epifluorescence microscopy was implemented to recognize specific morphologies like microcolonies or single cells (7), and the number of clustered cells (at least for size classes of aggregates) (13)(14)(15).…”
mentioning
confidence: 99%